Digital Strategies for Marketing Relationships with Customers (European Journal of Marketing and Economics, 2022)
In the conditions of the new economy and in the spirit of the relationship marketing and corporate social responsibility, the digital strategies of building bonds with the consumer are a major area for competitiveness. The present report suggests a model of digital marketing strategies for bonds between a business entity and a client. Based on a study of 303 consumers and 78 companies, consumer opinions about the role of the instruments of the major strategies for mutual bonds—strategies for retention, attraction, and development of a bond—were analyzed. There is analysis of the digital communication tools and principles most used by the companies. The comparative analysis of the results of the research allows the formulation of recommendations for the business entities for the application of a package of digital tools for bonds with the consumers and the improvement of the results of these activities.
Keywords: marketing relationships, digital strategies, digital marketing tools, relationships with customers